Ergosterone-coupled Triazol molecules trigger mitochondrial dysfunction, oxidative stress, and acidocalcisomal Ca2+ release in Leishmania mexicana promastigotes - Figarella K; Marsiccobetre S; Arocha I; Colina W; Hasegawa M; Rodriguez M; Rodriguez-Acosta A; Duszenko M; Benaim G; Uzcategui NL (Microbial Cell)
The protozoan parasite Leishmania causes a variety of sicknesses with different clinical manifestations known as leishmaniasis. The chemotherapy currently in use is not adequate because of their side effects, resistance occurrence, and recurrences. Investigations looking for new targets or new active molecules focus mainly on the disruption of parasite specific pathways. In this sense, ergosterol biosynthesis is one of the most attractive because it does not occur in mammals. Here, we report the synthesis of ergosterone coupled molecules and the characterization of their biological activity on Leishmania mexicana promastigotes. Molecule synthesis involved three steps: ergosterone formation using Jones oxidation, synthesis of Girard reagents, and coupling reaction. All compounds were obtained in good yield and high purity. Results show that ergosterone-triazol molecules (Erg-GTr and Erg-GTr2) exhibit an antiproliferative effect in low micromolar range with a selectivity index ~10 when compared to human dermic fibroblasts. Addition of Erg-GTr or Erg-GTr2 to parasites led to a rapid [Ca2+]cyt increase and acidocalcisomes alkalinization, indicating that Ca2+ was released from this organelle. Evaluation of cell death markers revealed some apoptosis-like indicators, as phosphatidylserine exposure, DNA damage, and cytosolic vacuolization and autophagy exacerbation. Furthermore, mitochondrion hyperpolarization and superoxide production increase were detected already 6 hours after drug addition, denoting that oxidative stress is implicated in triggering the observed phenotype. Taken together our results indicate that ergosterone-triazol coupled molecules induce a regulated cell death process in the parasite and may represent starting point molecules in the search of new chemotherapeutic agents to combat leishmaniasis.